Analysis of The Moderation Effect of Customer Innovativeness in Increasing Customer Loyalty Phygital Retail in the Culinary Industry - Novita Margareth Marta; Triyono Arief Wahyudib (Syntax Corporation Indonesia, 2023)
This research was conducted to analyze the Moderation Effects of Customer Innovativeness in increasing Phygital Retail Customer Loyalty in the Indonesian Culinary Industry. The purpose of this study is to analyze the application of the Phygital Retail concept in order to optimize Phygital Retail outlets in the Indonesian Culinary Industry. This research is a quantitative research with the PLS Structural Equation Modeling (SEM) approach. Sources of data in this study were obtained by distributing online questionnaires to respondents who were customers of outlets or Resto Phygital Retail. The results of this study state that as a form of effort towards optimizing Phygital Retail outlets that implement the Phygital Retail concept, it is hoped that consumers can carry out innovations which are encouragement from the consumers themselves to become more involved and loyal to the company, hence consumer involvement and loyalty. This can be achieved by implementing strategies in the Phygital Retail sales system that bring pleasure to consumers.